مقاصد الكتابة في القرآن الكريم = The purposes of writing in the Holy Qur’an - Badran, Fedaa Bassam; Elatrash, Radwan Jamal Yousef (IIUM Press, International Islamic University Malaysia, 2020)
يعد موضوع الكتابة من الموضوعات المهمة في القرآن الكريم؛ لتعلقها بالاجتهاد العقلي، ورغم كثرة الآيات التي تتحدث عن الكتابة إلا أن الحديث عن مقاصد الكتابة في القرآن الكريم يشكل تحديا ا للباحثين، وجاءت هذه الدراسة لبيان مقاصد الكتابة ومتعلقاتها في القرآن الكريم، وتكمن أهم ي ة البحث في اهتمام القرآن الكريم بالكتابة لأنها إحدى وسائل توثيق لكثير من القضايا، كالعقود المالية، والعلاقات الاجتماعية والسياسية، حيث ذكرت الكتابة بصفة صريحة في القرآن الكريم في حوالي مائتين وثمانين موضعاا، كما أ نها كانت وسيلة راقية في عهد الن بي ﷺ، خاطب بها الملوك والزعماء، ومن خلالها تم توثيق القرآن الكريم والسنة النبوية. واعتمد البحث المنهج الاستقرائي، من خلال جمع الآيات القرآنية التي تحدثت عن مقاصد الكتابة في القرآن الكريم، وذلك بالرجوع إلى برامج البحث في القرآن الكريم وكتب التفسير القديمة والحديثة، كما اعتمد المنهج التحليلي، وذلك بتفسير الآيات وتحليلها وتصنيفها ،واستنباط مقاصد الكتابة في القرآن الكر يم، ويب ين البحث أ ن من مقاصد الكتابة إثبات الحقوق المالية وبخاصة الديون من خلال كتابتها، وكذلك حفظ النسب وحقوق الزوجين من خلال توثيق عقود الزواج. ****************************************************************************** The topic of inscribing in the Holy Qur’an is one of the important topics at, because it is related to mental endeavor, and despite the many verses that speak about inscribing, talking about the objectives of inscribing in the Holy Qur'an is a challenge for researchers. This study illustrates the objectives of inscribing and its derivatives in the Holy Qur’an. The importance of this research lies in the interest of the Holy Qur’an in the subject of inscribing because it is one of the means through which many issues are documented, such as financial contracts, social and political relations, where inscribing is mentioned explicitly in the Holy Qur’an in about two hundred and eighty places. In addition, as it was a stylish means during the era of the Prophet Muhammad (Pace be upon him), who used it for addressing kings and leaders, and it was used for documentation of the Holy Qur’an and Sunnah. This research adopted the inductive methodology, by collecting Qur’anic verses that talked about the objectives of inscribing in the Holy Qur’an, by referring to search programs in the Holy Qur’an, and by referring to Tafsir books. The analytical methodology was also adopted in this research, by interpreting, analyzing, and categorizing verses, and deriving the objectives and semantics of inscribing in the Holy Qur’an. The research concludes with the objectives of inscribing in the Holy Quran such as to prove financial rights, especially debts, by writing a receipt, and another objective is to preserve the lineages and rights of spouses through the documentation of marriage contracts.